Evaluating air pollution exposures across cycling infrastructure types: Implications for facility design - William Jacob Farrell; Scott Weichenthal; Mark Goldberg; Marianne Hatzopoulou (Journal of Transport and Land Use)
Expanding urban cycling networks requires consideration of a number of important factors. Yet there exists no set of best practices and surprisingly little research detailing which sorts of cycling infrastructure may be better or worse in terms of exposure to harmful pollutants. A large air-quality data collection campaign was conducted in summer 2012 whereby cyclists equipped with ultrafine particle (UFP) and black carbon (BC) monitors covered over 550 kilometers of streets, including 325 kilometers of designated cycling facilities on the Island of Montreal. The clearest result from this exercise is that pollution levels on trails, often far from vehicular streets, are markedly lower than cycling facilities located on or alongside the street. For in-street and separated facilities, both UFP and BC were more closely associated with the hierarchy of the street than the type of cycling facility. Between in-street and separated facilities, the difference in UFP levels was not statistically significant. However, the difference between BC levels on in-street and separated facilities was significant, with separated facilities yielding lower concentrations. Ultimately, more research is needed to understand the potential efficacy of facility and network design as a pollution exposure abatement measure; however, these findings show moderate advantages of separated facilities over in-street facilities and more substantial advantages for off-road facilities over either.